Exogenous testosterone administration is associated with differential neural response to unfamiliar peer's and own caregiver's voice in transgender adolescents. (February 2023) - Morningstar, Michele; Thomas, Peyton; Anderson, Avery M.; Mattson, Whitney I.; Nahata, Leena; Leibowitz, Scott F.; Chen, Diane; Strang, John F.; Nelson, Eric E.
Abstract: Changes in gonadal hormones during puberty are thought to potentiate adolescents' social re-orientation away from caregivers and towards peers. This study investigated the effect of testosterone on neural processing of emotional (vocal) stimuli by unfamiliar peers vs. parents, in transgender boys receiving exogenous testosterone as a gender-affirming hormone (GAH+) or not (GAH-). During fMRI, youth heard angry and happy vocal expressions spoken by their caregiver and an unfamiliar teenager. Youth also self-reported on closeness with friends and parents. Whole-brain analyses (controlling for age) revealed that GAH+ youth showed blunted neural response to caregivers' angry voices—and heightened response to unfamiliar teenage angry voices—in the anterior cingulate cortex. This pattern was reversed in GAH- youth, who also showed greater response to happy unfamiliar teenager vs. happy caregiver voices in this region. Blunted ACC response to angry caregiver voices—a pattern characteristic of GAH+ youth—was associated with greater relative closeness with friends over parents, which could index more "advanced" social re-orientation. Consistent with models of adolescent neurodevelopment, increases in testosterone during adolescence may shift the valuation of caregiver vs. peer emotional cues in a brain region associated with processing affective information. Highlights: Exogenous testosterone was linked to shifts in ACC response to peer/parent voices. These neural patterns were related to increased closeness with peers over parents. Findings were aligned with expected social re-orientation processes in adolescence.